Breastfeeding Among Minority Women: Moving From Risk Factors to Interventions(1)(2) - Chapman, Donna J. (American Society for Nutrition, 2012)
The gap between current breastfeeding practices and the Healthy People 2020 breastfeeding goals is widest for black women compared with all other ethnic groups. Also of concern, Hispanic and black women have the highest rates of formula supplementation of breast-fed infants before 2 d of life. These disparities must be addressed through the scale-up of effective interventions. The objective of this critical review is to identify and evaluate U.S.-based randomized trials evaluating breastfeeding interventions targeting minorities and highlight promising public health approaches for minimizing breastfeeding disparities. Through PubMed searches, we identified 22 relevant publications evaluating 18 interventions targeting minorities (peer counseling [n = 4], professional support [n = 4], a breastfeeding team [peer + professional support, n = 3], breastfeeding-specific clinic appointments [n = 2], group prenatal education [n = 3], and enhanced breastfeeding programs [n = 2]). Peer counseling interventions (alone or in combination with a health professional), breastfeeding-specific clinic appointments, group prenatal education, and hospital/Special Supplemental Nutrition Program for Women, Infants, and Children enhancements were all found to greatly improve breastfeeding initiation, duration, or exclusivity. Postpartum professional support delivered by nurses was found to be the least effective intervention type. Beyond improving breastfeeding outcomes, 6 interventions resulted in reductions in infant morbidity or health care use. Future research should include further evaluations of successful interventions, with an emphasis on determining the optimal timeframe for the provision of support, the effect of educating women’s family members, and the impact on infant health care use and cost-effectiveness.